Mitogenome of Mytilus trossulus (Mytilidae, Bivalvia) isolated from a 1920 herbarium specimen. Issue 1 (1st January 2016) - Hughey, Jeffery R.; Boo, Ga Hun; Boo, Sung Min
Abstract: DNA was extracted from a red algal herbarium specimen collected in 1920 and subjected to next generation sequencing. Here we report the assembly of the mitogenome of a marine mussel, Mytilus trossulus, deciphered from this plant museum specimen. The mitogenome is 16, 744 bp in length, contains 38 genes, and is more similar to other M. trossulus reported from the Baltic Sea. The data show that in addition to plant DNA, herbarium specimens also contain genetic information from invertebrates that may be valuable for genomic, population and phylogenetic studies of animals.